Feasibility of Detecting Brain Areas Involved in Extreme Breath-Hold Diving - Jissendi-Tchofo, Patrice; Jdaoudi, Yassin; Germonpré, Peter; Cialoni, Danilo; Brizzolari, Andrea; Musimu, Patrick; Balestra, Costantino (Journal of Neurological Research And Therapy, 2021)
A feasibility study explores neuroimaging approaches to identify brain regions engaged during extreme breath‑hold diving. Methods, safety considerations, and preliminary activation patterns are summarized to motivate further controlled studies.
Keywords: breath-hold protocol; fMRI technique; Cerebral Decompression illness